2018
DOI: 10.1136/heartjnl-2017-312774
|View full text |Cite
|
Sign up to set email alerts
|

Danegaptide for primary percutaneous coronary intervention in acute myocardial infarction patients: a phase 2 randomised clinical trial

Abstract: NCT01977755; Pre-results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…These cardioprotective effects, however, appeared independent of mitoCx43 [139]. Finally, a clinical proof-of-concept Phase II study on 585 patients with ST-segment elevation myocardial infarction (STEMI) showed that danegaptide, administered at least 10 min prior to reperfusion, did not improve myocardial salvage [140].…”
Section: Concluding Remarks: On the Way Towards Cx43-targeted Strategmentioning
confidence: 99%
“…These cardioprotective effects, however, appeared independent of mitoCx43 [139]. Finally, a clinical proof-of-concept Phase II study on 585 patients with ST-segment elevation myocardial infarction (STEMI) showed that danegaptide, administered at least 10 min prior to reperfusion, did not improve myocardial salvage [140].…”
Section: Concluding Remarks: On the Way Towards Cx43-targeted Strategmentioning
confidence: 99%
“…Finally, the dipeptide ZP1609 (danegaptide) has antiarrhythmic properties and has been shown to reduce infarct size following ischemia/ reperfusion in pigs [96]. Nevertheless, this GJ coupling-modulating peptide failed to improve myocardial salvage in patients with ST-elevation myocardial infarction (STEMI) in a Phase II randomized clinical trial [97]. It is promising that multiple tools interfering with Cx43 expression, its interactome, or channel function have appeared in recent years, yet many questions still need to be addressed regarding their exact working mechanisms as well as their specificity and stability in organisms.…”
Section: Therapeutic Strategies Targeting Cx43mentioning
confidence: 99%
“…However, a recently published phase II study did not confirm the early results. 27 Other enhancers of GJ function such as ACT1, a peptide that mimics the carboxyl terminus of Cx43, have been evaluated in cutaneous ulcers 28 and arrhythmias, where they led to wound re-epithelialization and reduced inducible arrhythmias following ventricular injury, respectively. 29 Conversely, strategies that target specific Cxs with antisense oligonucleotide and mimetic peptides can be used if the goal is to block intercellular communication.…”
Section: Modulators Of Gj Function and Targeting In Diseases Outside mentioning
confidence: 99%